Carbon Taxation and Firm Behavior in Emerging Economies: Evidence from South Africa - Johannes Galle; Rodrigo Oliveira; Daniel Overbeck; Nadine Riedel; Edson Severnini (Institute of Labor Economics (IZA), 2025)
This paper provides the first comprehensive evidence on how firms in emerging economies respond to carbon taxation. Using detailed administrative data, we study the announcement and implementation of South Africa's 2019 carbon tax—a potential trailblazer for other developing countries with limited state capacity amid the global expansion of carbon pricing. Contrary to concerns that carbon taxes might hinder growth or employment, we find no negative effects on firm performance or jobs. Firms facing higher effective tax rates increased activity following the tax's announcement, four years before implementation, likely reflecting the resolution of regulatory uncertainty and efforts to mitigate stranded asset costs. While we find no measurable reduction in emissions—likely due to this anticipatory behavior—our results suggest that carbon taxation can be implemented without harming economic outcomes, even in the short term and in low- and middle-income settings.
Keywords: H23; Q52; Q58; O13; O55; 330; carbon pricing; carbon tax; firm performance; employment outcomes